1993
DOI: 10.1002/jcp.1041540323
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor receptor deficiency in dystrophic retinal pigmented epithelium

Abstract: The retinal pigmented epithelium (RPE) is known to be the site of the primary lesion in inherited retinal dystrophy in the Royal College of Surgeons (RCS) rat, a model for retinitis pigmentosa. Although the only functional defect so far detected in these cells is their failure to efficiently phagocytose shed photoreceptor outer segment debris, the actual cause of photoreceptor cell death is still unknown. Recently the possibility of "trophic factors" important in photoreceptor survival produced by normal RPE b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 44 publications
1
20
2
1
Order By: Relevance
“…Our data have also shown that the labeling gradually decreased and almost completely disappeared in some organs 5 days postinjection of 14 C-FGF2, suggesting that FGF2 is under continuous cellular internalization, intracellular catabolism, and recycling of the resulting amino acids. The catabolic fragments of FGF2 that we have demonstrated in our study were similar in all organs and to those seen in FGF2 internalization and catabolism in vitro (Malecaze et al, 1993;Colin et al, 1997), reflecting similar intracellular processing of FGF2 in the different organs. In a recent in vitro study, we found two novel transitory catabolic fragments of the internalized FGF2 of 14 and 7 kDa (Colin et al, 1997), which could be the results of a very specific event or events in the intracellular processing of FGF2.…”
Section: Hspg Regulates the Bioavailability Of Fgf2 In Vivo 79supporting
confidence: 81%
See 1 more Smart Citation
“…Our data have also shown that the labeling gradually decreased and almost completely disappeared in some organs 5 days postinjection of 14 C-FGF2, suggesting that FGF2 is under continuous cellular internalization, intracellular catabolism, and recycling of the resulting amino acids. The catabolic fragments of FGF2 that we have demonstrated in our study were similar in all organs and to those seen in FGF2 internalization and catabolism in vitro (Malecaze et al, 1993;Colin et al, 1997), reflecting similar intracellular processing of FGF2 in the different organs. In a recent in vitro study, we found two novel transitory catabolic fragments of the internalized FGF2 of 14 and 7 kDa (Colin et al, 1997), which could be the results of a very specific event or events in the intracellular processing of FGF2.…”
Section: Hspg Regulates the Bioavailability Of Fgf2 In Vivo 79supporting
confidence: 81%
“…5B). The fragments resulting from the in vivo catabolism of 14 C-FGF2 were then compared with those previously described for the in vitro catabolism of this growth factor by RPE cells (Malecaze et al, 1993;Colin et al, 1997). It seems that the in vivo and in vitro catabolism of this growth factor produces similar catabolic fragments (i.e., of 16, 8, and 5.5 kDa) (Fig.…”
Section: Downloaded Frommentioning
confidence: 89%
“…It has been previously shown by RT ± PCR that normal RCS RPE cells express FGF2 mRNA (Malecaze et al, 1993). We con®rmed by Western blot that they were actively transcribed.…”
Section: Expression Of Vegf and Fgf2 In Transfected Rat Rpe Cellsmentioning
confidence: 54%
“…In culture, RPE cells produce FGF1 and FGF2 (Chen et al, 1996), FGF high a nity receptors (FGFR) and in particular FGFR1 (Guillonneau et al, 1997). In growing RPE cells, ERKs are rapidly and transiently activated in response to exogenous FGFs (Malecaze et al, 1993). We have shown that FGF2 stimulated the production of endogenous FGF1 (Guillonneau et al, 1997) and that high-level expression of endogenous FGF1 is correlated with a reduction in apoptosis during RPE cell aging (Guillonneau et al, 1998b).…”
Section: Introductionmentioning
confidence: 96%